A comparative study of ultrafine water mist extinguishing hydrocarbon pool fires with or without potassium salts. (1st March 2023) - Liang, Tianshui; Bai, Xiaolin; Zhang, Dongfang; Zhong, Wei
Highlights: Experimental and theoretical values of MECs of water mist was compared. The contribution of heat extraction of water mist for fire extinction was discussed. The MECs of potassium salts solution was obtained. The extinction of ethanol or n -heptanes fire with KOH solution was compared. The fire extinguishing mechanism of KOH(g) was discussed. Abstract: Potassium salt is a highest efficiency powder agent and water mist additive for fire suppression. In the literature, however, the comparison of K2 C2 O4 and K2 CO3 in fire extinguishing efficiency is still controversial. In the study, a model of calculating MEC of UFWM was developed based on heat extraction. The minimum extinguishing concentration (MEC) of ultra-fine water mist (UFWM) with and without potassium salt were obtained in an improved cupburner. Ethanol and n -heptanes were separately chose as the fuel of fire source. By comparing predicted value and experimental value of MECs, It is found that the contribution of heat capacity is less than 50 % in fire extinguishment, and it is supposed that turbulence effect generated by volume expansion of droplet evaporation play an important role in extinguishing fire. Based on mole concentration, the efficiency of the potassium salts solution extinguishing fire is K2 C2 O4  > CH3 COOK > KNO3  > K2 CO3  > KOH > KCl > KH2 PO4 ( n -heptanes fire), and K2 C2 O4  > CH3 COOK > KNO3  > K2 CO3  > KCl > KOH > KH2 PO4 (ethanol fire). The primary fire extinguishing mechanism of KOH (g) is removing H radicals through two reaction pathways: K(g) + H(g) → KH(g), KH(g) + H(g) → K(g) + H2 (g) and KO(g) + H(g) → KOH(g), KOH(g) + H(g) → K(g) + H2 O(g); and the elimination of OH is through the reactions: K(g) + OH(g) → KOH(g) and KH(g) + OH(g) → K(g) + H2 O. Turbulence effect also is an important on combustion and extinguish flames; and the order of turbulence effects for fire extinguishment is K2 C2 O4  > CH3 COOK > KNO3 .